2004
DOI: 10.1093/cercor/bhh120
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical Responses in Human and Monkey Primary Auditory Cortex Support a Temporal Processing Mechanism for Encoding of the Voice Onset Time Phonetic Parameter

Abstract: This study tests the hypothesis that temporal response patterns in primary auditory cortex are potentially relevant for voice onset time (VOT) encoding in two related experiments. The first experiment investigates whether temporal responses reflecting VOT are modulated in a way that can account for boundary shifts that occur with changes in first formant (F1) frequency, and by extension, consonant place of articulation. Evoked potentials recorded from Heschl's gyrus in a patient undergoing epilepsy surgery eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
83
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 113 publications
13
83
1
Order By: Relevance
“…In humans, identifying a separation of two acoustic events requires stimulus onset asynchrony of ϳ20 ms (Pisoni, 1977;Pastore, 1983;Stevens and Weaver, 2005). Auditory cortical neurons were also found to have a similar limitation in representing two separated sounds (Eggermont, 1995;Steinschneider et al, 2003Steinschneider et al, , 2005. Moreover, the spike timing of A1 neurons has been proved to convey sufficient information to discriminate slow changes (Ͻ50 Hz) in the envelopes of complex sounds, if the spike information is read at temporal resolutions of 20 ms or better (Walker et al, 2008).…”
Section: Temporal Resolution Of Neural Responsementioning
confidence: 99%
“…In humans, identifying a separation of two acoustic events requires stimulus onset asynchrony of ϳ20 ms (Pisoni, 1977;Pastore, 1983;Stevens and Weaver, 2005). Auditory cortical neurons were also found to have a similar limitation in representing two separated sounds (Eggermont, 1995;Steinschneider et al, 2003Steinschneider et al, , 2005. Moreover, the spike timing of A1 neurons has been proved to convey sufficient information to discriminate slow changes (Ͻ50 Hz) in the envelopes of complex sounds, if the spike information is read at temporal resolutions of 20 ms or better (Walker et al, 2008).…”
Section: Temporal Resolution Of Neural Responsementioning
confidence: 99%
“…The context, or environment surrounding a probe tone, modulates the amplitude of both single-and multi-unit neural activity. Contextual factors such as temporal sound density (Blake and Merzinich, 2002;Brosch and Schreiner, 2000), temporal onset time (Steinschneider et al, 2005), interaural phase disparity (Malone et al, 2002), or forward (Brosch and Schreiner, 1997;Fishman et al, 2004) and backward (Brosch et al, 1998) masking, arising from properties of adjacent sounds, have been shown to influence the way that auditory cortical neurons respond to the probe tone. What is unique in the current study is that the cortically generated response to the probe tone was modified by sounds not in its immediate proximity.…”
Section: Context-dependent Encoding Of Auditory Information In Auditomentioning
confidence: 99%
“…Next to their clinical importance, invasive recordings offer unique opportunities for electrophysiological investigations of human brain function with high spatial and temporal accuracy. An increasing number of studies have recently investigated motor Brovelli et al, 2005;Crone et al, 1998;Rektor, 2000;Szurhaj et al, 2006), sensory (Crone et al, 2001a;Edwards et al, 2005;Steinschneider et al, 2005), and cognitive (Canolty et al, 2006;Crone et al, 2001b;Ray et al, 2008;Sederberg et al, 2007;Sinai et al, 2005) systems using invasive EEG data. Furthermore, ECoG recordings have been proposed as a technology for brain-machine interfaces (BMIs) for neuronal motor prostheses in paralyzed patients (Ball et al, 2009;Leuthardt et al, 2004;Mehring et al, 2004;Pistohl et al, 2008;Schalk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%